Non‐invasive in vivo tracking of fibrin degradation by fluorescence imaging. (6th July 2014) - Wolbank, Susanne; Pichler, Valentin; Ferguson, James Crawford; Meinl, Alexandra; van Griensven, Martijn; Goppelt, Andreas; Redl, Heinz
Abstract Fibrin‐based sealants consist of natural coagulation factors involved in the final phase of blood coagulation, during which fibrinogen is enzymatically converted by thrombin to form a solid‐phase fibrin clot. For applications in tissue regeneration, a controlled process of matrix degradation within a certain period of time is essential for optimal wound healing. Hence, it is desirable to follow the kinetics of fibrinolysis at the application site. Non‐invasive molecular imaging systems enable real‐time tracking of processes in the living animal. In this study, a non‐invasive fluorescence based imaging system was applied to follow and quantify site‐specific degradation of fibrin sealant. To enable non‐invasive tracking of fibrin in vivo, fibrin‐matrix was labelled by incorporation of a fluorophore‐conjugated fibrinogen component. Protein degradation and release of fluorescence were, in a first step, correlated in vitro. In vivo, fluorophore‐labelled fibrin was subcutaneously implanted in mice and followed throughout the experiment using a multispectral imaging system. For the fluorescent fibrin, degradation correlated with the release of fluorescence from the clots in vitro. In vivo it was possible to follow and quantify implanted fibrin clots throughout the experiment, demonstrating degradation kinetics of approximately 16 days in the subcutaneous compartment, which was further confirmed by histological evaluation of the application site. Copyright © 2014 John Wiley & Sons, Ltd.